2012
DOI: 10.1007/s00436-012-3136-y
|View full text |Cite
|
Sign up to set email alerts
|

Myxobolus musseliusae (Myxozoa: Myxobolidae) from the gills of common carp Cyprinus carpio and revision of Myxobolus dispar recorded in China

Abstract: During a survey of myxozoan parasites of common carp Cyprinus carpio in Honghu Lake, Hubei Province, China, a parasite was collected that was identified as Myxobolus dispar based on an earlier description from China. However, the small subunit ribosomal DNA of this species shared only 90 % similarity with M. dispar, instead matching M. musseliusae with 100 % identity. To resolve this apparent taxonomic conflict, the validity of M. dispar reported from China was investigated. The species encountered here and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The reported species in the present work were highlighted in bold and species with spores of blunted anterior end underlined challenges the traditional taxonomy (Bahri 2008;Liu et al 2010Liu et al , 2014Zhang et al 2014) and suppression of Henneguya was also suggested (Kent et al 2001). In the present study, caudal appendages were firstly reported for some of spores of M.miyairii which is the ninth reported Myxobolus species with tailed spores after M. bizerti, M. mulleri, M. heterosporus, M. turpisrotundus, M. musseliusae, M. tsangwuensis, M. oralis, and M. khaliji (Bahri 2008;Liu et al 2010Liu et al , 2013Liu et al , 2014Zhang et al 2014). Interesting, two types of tailed spores (single tail or bifurcated tail) were firstly observed from most of plasmodia of M. miyairii which make it distinguished from the definition of Henneguya.…”
Section: Discussionsupporting
confidence: 54%
“…The reported species in the present work were highlighted in bold and species with spores of blunted anterior end underlined challenges the traditional taxonomy (Bahri 2008;Liu et al 2010Liu et al , 2014Zhang et al 2014) and suppression of Henneguya was also suggested (Kent et al 2001). In the present study, caudal appendages were firstly reported for some of spores of M.miyairii which is the ninth reported Myxobolus species with tailed spores after M. bizerti, M. mulleri, M. heterosporus, M. turpisrotundus, M. musseliusae, M. tsangwuensis, M. oralis, and M. khaliji (Bahri 2008;Liu et al 2010Liu et al , 2013Liu et al , 2014Zhang et al 2014). Interesting, two types of tailed spores (single tail or bifurcated tail) were firstly observed from most of plasmodia of M. miyairii which make it distinguished from the definition of Henneguya.…”
Section: Discussionsupporting
confidence: 54%
“…was not a valid feature for characterisation of the genus. Recently, some Myxobolus species have been reported with appendages similar to those of Henneguya species (ElMansy 2005, Bahri 2008, Liu et al 2010b, 2013a, which supports the opinion of Kent et al (2001). In the present study, we also observed 11% of the spores with caudal appendage.…”
Section: Referencessupporting
confidence: 91%
“…Henneguya, Hennegoides, Unicauda, Dicauda, Tetrauronema, Thelohanellus, Neothelohanellus and Phlogospora). The Myxobolus morphotype and its variations are thus associated with over 1,100 species-some 50 % of myxosporean species described to date (Lom and Dyková 2006;Liu et al 2013). The success of the Myxobolus morphotype may relate to the lateral flattening of spores that enabled invasion of tissues from precursors that lived in organ cavities and then subsequently radiated to exploit a range of niches offered by different tissues.…”
Section: Myxosporean Spore Morphotypes Drivers Of Diversification Anmentioning
confidence: 97%
“…The most common myxospore morphotype is that of Myxobolus, a genus which has diversified to more than 800 species histozoic in fish (Liu et al 2013). Many myxospore morphotypes associated with other tissue-dwelling genera appear to be modifications of this relatively simple morphotype, varying in only minor ways (e.g.…”
Section: Myxosporean Spore Morphotypes Drivers Of Diversification Anmentioning
confidence: 99%